Relations of war and peace between al-Zahir Baybars and the Nuba kings - حسن, غادة; عباس, بشار; زهرة, مازن (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Al-Zahir Baybars’ relations and conflict with the kings of Nubia are inseparable from the traditional conflict between East and West, specifically between the Muslim East and the Christian West. The popes of the West do not wish to see a strong Muslim state on the other side of the Mediterranean, competing with them in matters of trade, and controlling European pilgrimage places They had previously tried to carry out an armed pilgrimage called the Crusades, and it continued in various forms, including supporting the states surrounding the Mamluks, so they carried out harassment on their borders, the Mamluks responded with force and launched campaigns that resolved the situation, and brought the Nubians out of the conflict, as an arm of the Christian West, according to conditions set and imposed by the Mamluks.